Baclofen Intoxication - Canan Bor; İclal Karaca; Özge Karakoç; İlkin Çankayalı; Kubilay Demirağ; Mehmet Uyar (Galenos Yayinevi, 2015)
Baclofen is a β-(ρ-chlorophenyl) derivative of the neurotransmitter gamma-aminobutyric acid (GABA) and is usually prescribed for spasticity of spinal cord origin, intractable hiccup, trigeminal neuralgia, hemifacial spasm, and tardive dyskinesia. The usual recommended daily dose ranges from 40-80 mg, and the total dose should not exceed 80 mg per day. A 41 year old woman using baclofen for migraine therapy intended suicide after a bitter headache attack by taking 37 tablets, 10 mg in each. On arrival to emergency room, she was conscious and co-operable, but somnolent, her pupils were normoisocoric and light reflex was intact bilaterally. On her follow up, respiratory insufficiency and unconsciousness was observed so she was entubated orotracheally and transferred to intensive care unit (ICU) for advanced tests and therapy. No pathology was determined on cranial CT. On ICU follow up, she was unconscious and mechanically ventilated, her Glasgow Coma Scale was 3/15 (E1M1VE) and pupils were mid-dilated with no light reflex. Since she was again conscious, oriented and co-operable on 19th hour of arrival to ICU and 20th hour of arrival to emergency room, spontaneous breathing trials was started. Extubation was carried out on her 31th hour of arrival to ICU and 32th hour of arrival to emergency room. In conclusion; since baclofen overdose may cause deep coma, it should also be included in differential diagnosis. According to our opinion, performing diagnostic toxicological tests is not always possible that's why history and physical examination is fundamental in case of baclofen intoxication and we can get good results by giving frequent neurological examination, supportive and extracorporeal therapy in such a case.